2018
DOI: 10.1002/tafs.10040
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Responses of Alligator Gar Populations to Harvest under Various Length‐Based Regulations: Implications for Conservation and Management

Abstract: Interest in managing Alligator Gar Atractosteus spatula populations as a unique sport fishery has increased over the past decade, but despite this interest population responses to harvest are poorly understood. Fishing regulations for Alligator Gars vary throughout their distribution; however, to date most regulations have focused on a daily creel limit. We developed an age‐structured dynamic‐pool model in R to (1) quantify the population‐level effects of exploitation and (2) evaluate how these effects would b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Bow n and gars have persisted for millions of years. Fortunately, the negative perception of holosteans as "trash shes" 103 is changing to include greater appreciation for their evolutionary, ecological, and cultural importance 104 and, as shown here, their signi cance for understanding vertebrate genome biology. As the Amia genus may not be monotypic 2,105 , our genome assembly will be of utmost importance to evaluate bow n's species status and conservation.…”
Section: Discussionmentioning
confidence: 96%
“…Bow n and gars have persisted for millions of years. Fortunately, the negative perception of holosteans as "trash shes" 103 is changing to include greater appreciation for their evolutionary, ecological, and cultural importance 104 and, as shown here, their signi cance for understanding vertebrate genome biology. As the Amia genus may not be monotypic 2,105 , our genome assembly will be of utmost importance to evaluate bow n's species status and conservation.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, we considered the estimate to represent total rather than natural mortality. We described growth for each sex using three candidate growth models: (1) a traditional von Bertalanffy growth model (VBGM; von Bertalanffy 1938) used to represent asymptotic growth, (2) a power model, which has been used to represent nonasymptotic growth in the Alligator Gar (Buckmeier et al 2016;Smith et al 2018), and (3) the 536 biphasic double von Bertalanffy growth model (DVBGM; Porch et al 2002), which McGrath et al (2016 found to provide the best description of growth in the Longnose Gar Lepisosteus osseus. In addition to the maximum theoretical length (i.e., L inf ) parameter generated by the traditional VBGM, the DVBGM generates a t crit parameter, which identifies the pivotal age when the rate of growth towards L inf changes, as well as stage-specific instantaneous growth rate coefficients (i.e., k 1 and k 2 ) and age intercept parameters (i.e., t 1 and t 2 ; Porch et al 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Lost access to floodplain spawning habitats, along with long-term eradication efforts due to historic misconceptions of their impacts on more desirable fishes, has negatively affected many populations. More recently, increasing angling pressure has been observed on remaining stocks because their large body size and distinctive characteristics have made Alligator Gar popular among trophy-oriented anglers (Ross et al 2001;Smith et al 2018). For periodic life history strategists like the Alligator Gar (Winemiller and Rose 1992), even low exploitation rates (less than 5%) can result in growth and recruitment overfishing (Boreman 1997;Quist et al 2002;Smith et al 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This large, long-lived species was designated as vulnerable by the American Fisheries Society in 2008 following population declines and extirpation from the northern areas of its native range. In the United States, 10 of the 14 southeastern states within the historical range of Alligator Gars are actively managing populations through regulated harvest and/or reintroduction programs (Smith et al 2018). Reintroduction programs employ aquaculture to produce individuals for stocking.…”
mentioning
confidence: 99%